Prospects and Problems of Indian Retailing - Baseer, Amatul; Laxmi Prabha, G. (Indian Journal of Marketing, 2007)
Retail environment in India has evolved tremendously over the last 10 years. India is currently the ninth largest retail market in the world. And it is names of small towns like Dehradun, Vijaywada, Lucknow and Nasik that will power India up the rankings soon. With the emergence of organized retailing in the country and a growing convenience, retailing has emerged, as a key business, given their wide retail presence, exists customer base and strategically located sites. Even though India has well over 5 million retail outlets of all sizes and styles, the country sorely lacks anything that can resemble a retailing industry in the modern sense of term. Indian retailing though enjoys many unique features is still done in a primitive way, they were handicapped by higher taxes, multiple laws, wrong policy decisions, unnecessary/illegal imports, poor infrastructure and logistics, high cost of equipment and packing material. So in this paper an attempt has been made to discuss the current prospects and problems of retailing in India.